The Influence Of E-Service Quality On The Customer Satisfaction In Bandung - Assifa, Rima Martiannisa; Irawan, Herry (eProceedings of Management, 2024)
With the rapid development of technology today, people do digital activities everyday. The benefits of technologicaldevelopment felt by the community are that online food delivery (OFD) are increasingly popular. Gofood is a fooddelivery service provided by Gojek and has worked with more than hundrends of thousands of merchants throughoutIndonesia. Gofood is run by motorcycle, taxi drivers who have become Gojek members. The number of Goekdrivers makes ordering Gofood services faster. The purpose of this study is how much influence e-service quality hasan customer satisfaction with Gofood services. The metjod used in this research is qquantitaive method withdescriptive approach. Likert scale is used as a measurement scale and the data analysis used is multiple linearregression, partial test (t-test), simultaneous test (F test) and the coefficient of determination. In this study using nonprobability sampling techniques with purposive sampling type. By sing the Bernoulli formul, the the questionnairewas distributed to 400 respondents and data processing using SPSS. The research results from descriptive analysisreveal that the variable studied, namely e- service quality and customer satisfaction, are in the good category with apercentage of each variable, namely e-service quality of 74.4% and customer satisfaction of 74.8%. then for theresults of hypothesis testing both partially and simultaneously, both show that there is a significant influence betweene-service quality on Gofood customer satisfaction in Bandung. The contribution of the influence of the independentvariable e-service quality on the dependent variable customer satisfaction is 69.8%, while the remaining 30.2% isthe contribution of the influence of other variables outside this study such as e-strust, product and price. Keywords-e-service quality,customer satisfaction